How Can Maternal Age and Amount of Parity Affect the High Degree of Perineum Laceration and Neonatal Asphyxia in Vacuum Extraction Labor? - Ahmad Faiz Tobari; Tun Paksi Sareharto; Vannya Dewi Puspitasari; Nurul Setiyorini (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Complications that often occur in vacuum extraction are third and fourth degree lacerations and neonatal asphyxia. In addition, asphyxia is the third leading cause of infant mortality in the world. Apart from being influenced by the existing vacuum extraction factors, the incidence of neonatal asphyxia and perineum laceration is also influenced by several maternal factors including maternal age and maternal parity.Objective: To prove the relationship between maternal age and parity number with perineum laceration and neonatal asphyxia after vacuum extraction at Dr. Kariadi General Hospital Medical CentreMethods: This study was an analytic observational study with a cross-sectional approach. The minimum sample required in this study is 26 patient data. The data used were data from the medical records of vacuum extraction patients at dr. Kariadi General Hospital Medical Centre Semarang which fit the inclusion and exclusion criteria by means of consecutive sampling. Then the data that has been collected is analyzed to find the relationship between variables.Results: Mothers who gave birth with the aid of vacuum extraction who suffered the most from third and fourth degree lacerations (31%) and neonatal asphyxia (15%) were women who were at risk (27%) and had the amount of parity at risk (23%). Chi-square test showed that there was a significant relationship between maternal age with perineum lacerations (p = 0.014), maternal age with neonatal asphyxia (p = 0.047), total parity with perineum lacerations (0.004), total parity with neonatal asphyxia (p = 0.028).Conclusion: There is a relationship between maternal age and parity with perineum lacerations and neonatal asphyxia after vacuum extraction in Dr. Kariadi General Hospital Medical Centre Semarang. The incidence of grade 3 and 4 perineum lacerations and neonatal asphyxia was most prevalent in women at risk age more than 35 years and at risk parity, namely primiparous The most influential risk factors for the occurrence of grade 3 and 4 perineum lacerations and neonatal asphyxia are primiparity.